The relationship between test protocol and the development of exercise-induced hypoxemia (EIH) in highly trained athletes - Lama, I. L.; Wolski, L. A.; Coutts, K. D. (European Journal of Applied Physiology, 1996)
Healthy male endurance-trained cyclists [n = 11, age = 27.3 (3.9) years; mass = 73.0 (9.3) kg; height = 180.5 (6.9) cm; maximal oxygen consumption (VO2max) = 71.1 5.8) ml.kg-1.min-1, mean +/- (SD)] were recruited to assess the relationship between test protocol and the development of desaturation of arterial hemoglobin with oxygen, during incremental exercise tests to maximal aerobic capacity (VO2max). All subjects demonstrated resting pulmonary function within normal limits [forced vital capacity (FVC) = 6.0 (0.9); forced expiratory volume (FEV1.0) = 4.9 (0.6); FEV1.0/FVC = 0.8 (0.1)] and completed three ramped VO2max tests (Mijnhardt KEM-3 electronically braked cycle ergometer) beginning at 0 W with increments of either 20,30 or 40 W.min-1. All periods of testing were separated by a minimum of 72 h. VO2max, peak minute ventilation (VEpeak) (Medical Graphics, CPX-D), peak heart rate (fcpeak), peak power output (Wpeak), and minimum percentage arterial oxyhemoglobin saturation (% SaO2min) (Omeda Biox 3740 pulse oximeter) were determined. There were no significant differences (p > 0.05) in VEpeak [191.5 (26.2), 196.0 (24.4), 194.3 (23.9) l.min-1] fcpeak [191.4 (7.0), 190.3 (5.5), 187.8 (5.9) beats.min-1], VO2max [5.0 (0.5), 5.1 0.4), 5.1 (0.5) l.min-1] or %SaO2min [89.5 (1.5), 89.6 (1.3), 90.0 (2.3)] between protocols. The 20-W protocol [417 (27) W] demonstrated significantly lower Wpeak (P < 0.05) than the 30-W (434 (36) W] and 40-W [453 (38) W] protocols, indicating that peripheral fatigue may play an important factor in response to these tests. The results of this study demonstrate that arterial desaturation occurs as a result of intense exercise in highly trained athletes independent of the rate of attainment of VO2max.